PENERAPAN ALGORITMA K-MEANS CLUSTERING UNTUK PENCATATAN PENCAPAIAN KINERJA KARYAWAN - Imam Utomo; Ilka Zufria; Muhammad Siddik Hasibuan (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2024)
Abstract: This study aims to classify employee performance using the K-Means method. Employee data includes total orders, average order processing time, customer satisfaction, delivery errors, absences, successful projects, and training attended. The clustering process begins with calculating the initial centroid distance and grouping the data based on the nearest distance, repeated until there are no significant changes in the centroid positions. Clustering results are displayed in the "Result" feature with three performance categories: Excellent (C1), Satisfactory (C2), and Poor (C3). The final centroids are as follows: Centroid 1 (C1) = [0.53, 0.40, 0.64, 0.33, 0.31, 0.55, 0.50], Centroid 2 (C2) = [0.11, 0.82, 0.24, 0.78, 0.75, 0.13, 0.00], and Centroid 3 (C3) = [0.89, 0.12, 0.93, 0.11, 0.08, 0.87, 0.83]. The analysis shows 185 employees in cluster C1 (Excellent), 67 employees in cluster C2 (Satisfactory), and 383 employees in cluster C3 (Poor). These results can be used as a basis for managerial decision-making, such as training, promotion, or other actions to improve productivity and efficiency. The K-Means method has proven effective for employee performance clustering and can be well integrated into employee management systems. It is recommended to conduct a longitudinal study to observe changes in employee performance over time and measure the effectiveness of managerial interventions based on these clustering results. Keywords: K-Means Clustering, Employee Performance, Data Analysis, Performance                  Categories Abstrak: Penelitian ini bertujuan mengelompokkan kinerja karyawan import bagian opersional menggunakan metode K-Means. Data karyawan meliputi total order, rata-rata waktu proses order, kepuasan pelanggan, kesalahan pengiriman, absensi, proyek sukses, dan pelatihan yang diikuti. Proses clustering dimulai dengan menghitung jarak centroid awal dan mengelompokkan data berdasarkan jarak terdekat, diulang hingga tidak ada perubahan signifikan pada posisi centroid. Hasil clustering ditampilkan dalam fitur "Result" dengan tiga kategori kinerja: Baik (C1), Cukup (C2), dan Kurang (C3). Centroid akhir adalah sebagai berikut: Centroid 1 (C1) = [0.53, 0.40, 0.64, 0.33, 0.31, 0.55, 0.50], Centroid 2 (C2) = [0.11, 0.82, 0.24, 0.78, 0.75, 0.13, 0.00], dan Centroid 3 (C3) = [0.89, 0.12, 0.93, 0.11, 0.08, 0.87, 0.83]. Analisis menunjukkan 185 karyawan dalam cluster C1 (Baik), 67 karyawan dalam cluster C2 (Cukup), dan 383 karyawan dalam cluster C3 (Kurang). Hasil ini dapat dijadikan dasar untuk pengambilan keputusan manajerial, seperti pelatihan, promosi, atau tindakan lainnya yang meningkatkan produktivitas dan efisiensi. Metode K-Means terbukti efektif untuk pengelompokan kinerja karyawan dan dapat diintegrasikan dengan baik dalam sistem manajemen karyawan. Disarankan melakukan studi longitudinal untuk melihat perubahan kinerja karyawan dari waktu ke waktu dan mengukur efektivitas intervensi manajerial berdasarkan hasil clustering ini. Kata kunci: Pengelompokan K-Means, Kinerja Karyawan, Analisis Data, Kategori Kinerja